Can an Instrument Validated to Assess Parent–Child Interactions in the Laboratory Setting Be Applied to Home-Based Observations? - Lee, Helen H.; Ochoa, Nadia; Moragne-O'Neal, Nia; Rosales, Genesis F.; Pugach, Oksana; Shadamoro, Anuoluwapo; Martin, Molly A. (Frontiers in Pediatrics, 2021)
Background: The Toothbrushing Observations Scale (TBOS) was developed in a laboratory setting to measure child and parent behaviors during toothbrushing. However, we required an instrument to assess home based behaviors. We assessed the feasibility of applying TBOS to observations of parents and their child (< 3 years of age) in urban homes. Methods: Sample consisted of 36 families recruited from university and community pediatric dental/medical clinics and a Women, Infants, and Children center in Chicago as part of a pilot study for a larger clinical trial. The average age of children in our sample was 20.7 months. Most of the parent participants were mothers (90%) and 75% of the parents identified as Hispanic. Parent-child dyads were video-recorded during home-based toothbrushing activities and footage was reviewed by two independent TBOS coders. Results: The TBOS instrument consists of 12 parent and 18 child items. We were able to code five parent and ten child items. Conclusion: The feasibility of applying the TBOS measure to our study population was somewhat limited by factors related to home based observations and the young age of children in our study. Instruments need to be validated across natural settings, such as the home, to increase the quality and accuracy of human behavioral data.